The future generations of mobile communications based on broadband access technologies. - Ohmori, S. (IEEE Communications magazine)
The forthcoming mobile communication systems are expected to provide a wide variety of services, from high-quality voice to high-definition videos, through high data rate wireless channels anywhere in the world. The high data rate requires broad frequency bands, and sufficient broadband can be achieved in higher frequency bands such as microwave, Ka-band, and millimeter-wave. Broadband wireless channels have to be connected to broadband fixed networks such as the Internet and local area networks. The future-generation systems will include not only cellular phones, but also many new types of communication systems such as broadband wireless access systems, millimeter-wave LANs, intelligent transport systems, and high altitude stratospheric platform station systems. Key to the future generations of mobile communications are multimedia communications, wireless access to broadband fixed networks, and seamless roaming among different systems. This article discusses future-generation mobile communication systems.